Literature Review: Herbs to Prevent Nausea and Vomiting in Pregnant Women - Metty Nurherliyany; Rosidah Solihah; Ayu Endang Purwati; Sandriani Sandriani; Neng Mira (Nurul Ilmi : Journal of Health Sciences and Midwifery, 2023)
Introduction: Nausea and vomiting are experienced by pregnant women during early pregnancy and are often caused by hormonal changes due to an increase in the hormones estrogen, progesterone, and the release of human chorionic acid. Most pregnant women 70- 80% experience morning sickness and as many as 1-2% of all pregnant women experience it morning sickness which extreme. Ginger's pharmacological function is antiemetic, acting as an anti-vomiting agent. Objective: The purpose of this research is to review the literature, articles, and results documents of research on current activity interventions related to the effectiveness of giving herbal plants to reduce nausea and vomiting in pregnant women. Method: The method used in writing this article is a review of the results of a study that related to complementary therapies to reduce nausea and vomiting during pregnancy. The type of data used is secondary data. Sources of data in this literature review study were obtained by tracing scientific research articles from 2017 to 2022 using a data base such as Google Scholar, MyJM, and Science Direct, which included as many as five articles. Result: Initial treatment for nausea and vomiting should be conservative and accompanied by changes in diet, emotional support, and alternative therapies such as herbs. Ginger therapy can provide a more significant reduction in nausea and vomiting compared to leaf therapy, mint therapy, and kaffir lime therapy. In addition, ginger therapy, done together with hands-on massage or with vitamin B6 therapy, has a significant effect on overcoming nausea and vomiting during pregnancy. Conclusion: There is a significant effect of giving ginger therapy to reduce nausea and vomiting in the first trimester of pregnancy. Ginger therapy and the administration of vitamin B6 or hand massage can be an alternative therapy to help overcome nausea and vomiting in pregnant women.